Northern hemisphere glaciation during the globally warm early late Pliocene - De Schepper, Stijn; Groeneveld, Jeroen; Naafs, B. David A.; Van Renterghem, Cédéric; Hennissen, Jan; Head, Martin J.; Louwye, Stephen; Fabian, Karl (PLoS ONE, 2014)
The early Late Pliocene (3.6 to ,3.0 million years ago) is the last extended interval in Earth’s history when atmospheric CO2 concentrations were comparable to today’s and global climate was warmer. Yet a severe global glaciation during marine isotope stage (MIS) M2 interrupted this phase of global warmth ,3.30 million years ago, and is seen as a premature attempt of the climate system to establish an ice-age world. Here we propose a conceptual model for the glaciation and deglaciation of MIS M2 based on geochemical and palynological records from five marine sediment cores along a Caribbean to eastern North Atlantic transect. Our records show that increased Pacific-to-Atlantic flow via the Central American Seaway weakened the North Atlantic Current and attendant northward heat transport prior to MIS M2. The consequent cooling of the northern high latitude oceans permitted expansion of the continental ice sheets during MIS M2, despite near-modern atmospheric CO2 concentrations. Sea level drop during this glaciation halted the inflow of Pacific water to the Atlantic via the Central American Seaway, allowing the build-up of a Caribbean Warm Pool. Once this warm pool was large enough, the Gulf Stream–North Atlantic Current system was reinvigorated, leading to significant northward heat transport that terminated the glaciation. Before and after MIS M2, heat transport via the North Atlantic Current was crucial in maintaining warm climates comparable to those predicted for the end of this century. publishedVersion